The Nuclear Security Science and Policy Institute at Texas A&M University - Claudio A. Gariazzo; Kelley H. Ragusa; David R. Boyle; William S. Charlton; Sunil S. Chirayath; Craig M. Marianno; Paul Nelson Jr. (International Journal of Nuclear Security, 2015)
The Nuclear Security Science and Policy Institute (NSSPI) is a multidisciplinary organization at Texas A&M University and was the first U.S. academic institution focused on technical graduate education, research, and service related to the safeguarding of nuclear materials and the reduction of nuclear threats. NSSPI employs science, engineering, and policy expertise to: (1) conduct research and development to help detect, prevent, and reverse nuclear and radiological proliferation and guard against nuclear terrorism; (2) educate the next generation of nuclear security and nuclear nonproliferation leaders; (3) analyze the interrelationships between policy and technology in the field of nuclear security; and (4) serve as a public resource for knowledge and skills to reduce nuclear threats. Since 2006, over 31 Doctoral and 73 Master degrees were awarded through NSSPI-sponsored research. Forty-one of those degrees are Master of Science in Nuclear Engineering with a specialization in Nuclear Nonproliferation and 16 were Doctorate of Philosophy degrees with a specific focus on nuclear nonproliferation. Over 200 students from both technical and policy backgrounds have taken classes provided by NSSPI at Texas A&M. The model for creating safeguards and security experts, which has in large part been replicated worldwide, was established at Texas A&M by NSSPI faculty and staff. In addition to conventional classroom lectures, NSSPI faculty have provided practical experiences; advised students on valuable research projects that have contributed substantially to the overall nuclear nonproliferation, safeguards and security arenas; and engaged several similar academic and research institutes around the world in activities and research for the benefit of Texas A&M students. NSSPI has had an enormous impact on the nuclear nonproliferation workforce (across the international community) in the past 8 years, and this paper is an attempt to summarize the activities accomplished by NSSPI during this time and the future direction of the program.
Keywords: nuclear; safeguards; security; education; university